Advances in synaptic plasticity - Baudry, M.; Davis, Joel L., 1942-; Thompson, Richard F. (MIT Press, 2000)
Many neurons exhibit plasticity; that is, they can change structurally or functionally, often in a lasting way. Plasticity is evident in such diverse phenomena as learning and memory, brain development, drug tolerance, sprouting of axon terminals after a brain lesion, and various cellular forms of activity-dependent synaptic plasticity such as long-term potentiation and long-term depression. This book, a follow-up to the editors' Synaptic Plasticity (MIT Press, 1993), reports on the most recent trends in the field. The levels of analysis range from molecular to cellular and network, the unifying theme being the nature of the relationships between synaptic plasticity and information processing and storage. Contributors : Yael Amitai, Michel Baudry, Theodore W. Berger, Pierre-Alain Buchs, A.K. Butler, Franck A. Chaillan, Gilbert A. Chauvet, Marie-Françoise Chesselet, Barry W. Connors, Taraneh Ghaffari, Jay R. Gibson, Ziv Gil, Michel Khrestchatisky, Dietmar Kuhl, Carole E. Landisman, Gilles Laurent, Jim-Shih Liaw, David J. Linden, Katrina MacLeod, Henry Markram, W.V. Morehouse, Dominique Muller, J.A. Napieralski, Santiago Rivera, François S. Roman, Bernard Soumireu-Mourat, Oswald Steward, Mark Stopfer, F.G. Szele, Richard F. Thompson, Nicolas Toni, Bernard Truchet, Misha Tsodyks, K. Uryu, Ascher Uziel, Christopher S. Wallace, Yun Wang, Michael Wehr, Paul F. Worley, Xiaping Xie.